The Prussian, the Hawk, and the "Revealed Essay" - Wilburn, Ron (The Trumpeter, 2021)
It is commonly believed that Neo-Kantian moral theory is necessarily hostile to enlightened environmentalism. My argument: Kantians can acknowledge our obligations toward nature once they recognize the value that the aesthetics of the natural world have as a proving ground for moral judgment. Treating this as an empirical claim, I supplement it with Maurice Mendelbaum’s notion of “fittingness” and test it via appeal to a specific case study provided by the phenomenological expertise of the twentieth century nature writer Loren Eiseley. What emerges is a (very) broadly Kantian defense of ecologically responsible action which does not presuppose the intrinsic moral value of non-human nature.